Pengaruh Kesadaran Perpajakan, Sikap Rasional, Dan Sanksi Denda Terhadap Kepatuhan Wajib Pajak - Livia Oktrina Tonni Soekianto, Vidyarto Nugroho (Fakultas Ekonomi, Universitas Tarumanagara, 2021)
The purpose of this study is to examine empirically about the effect of tax awareness, rational attitude, and sanctions fines on taxpayer compliance in Payakumbuh. This study uses 100 samples who has a steady income in Payakumbuh obtained by nonprobability sampling method with purposive sampling technique. Data sourced from primary data in the form of a questionnaire and processed using multiple regression analysis techniques with the SPSS 23 version program. The results of the study show that tax awareness and rational attitude have a significant positive influence on taxpayer compliance, while sanctions fines has a significant negative influence on taxpayer compliance.